Biomass assessment of demersal fish resources on the continental shelf of Northern Brazil - Filho, Mutsuo Asano; Holanda, Francisco Carlos Alberto Fonteles; de Oliveira, Gilvaniere Batista (Arquivos de Ciências do Mar, 2017)
Demersal estuarine/marine resources contribute with about 80% of the fish production landed at Pará State, Brazil. Because of the commercial importance and the intense effort now exercised for the capture of the main fishing stocks, this study seeks to evaluate their abundance by means of shrimp trawlnet surveys on the continental shelf between Cape Orange and the limits of Pará/Maranhão States. Variations of the catch per unit area (CPUA) were analyzed taking into account the seasonal influence of the rainy and dry seasons on catch rates as well as the relative abundance for the whole area and the main captured species. The estimated biomass of the demersal resources caught with shrimp trawlnets showed to be practically equal for the two portions of the continental shelf (up to 200 m), no differential influence being found during the dry and rainy seasons on CPUA values. Biomass was estimated as 95,649 tons, being weakfish, Macrodon ancylodon, the most abundance specie with16.07% of the whole fish biomass. Brown shrimp, Farfantepenaeus subtilis, which had appeared as the main species captured in previous surveys, in the presente sutdy had its participation decreased to only 5.92% of the estimated biomass.